Coalescent methods for fine-scale disease-gene mapping. - Morris, A (2007)
Fine-scale mapping methods have been developed to localize functional polymorphisms within large candidate regions identified from previous linkage and/or association studies. Population-based association fine-mapping methods utilize linkage disequilibrium of alleles at high-density marker single-nucleotide polymorphisms with the functional polymorphism, generated as the result of shared ancestry of individuals within the population. Here, we review fine-mapping methods that model the shared ancestry of sampled chromosomes explicitly, using the coalescent process, resulting in greater accuracy and precision to localize functional polymorphisms than approaches that treat individuals as unrelated.